Downregulation of Tryptophan-related Metabolomic Profile in Rheumatoid Arthritis Synovial Fluid - Kang, Kwi Young; Lee, Soo Hyun; Jung, Seung Min; Park, Sung-Hwan; Jung, Byung-Hwa; Ju, Ji Hyeon (Journal of Rheumatology Publishing Co., Ltd., 2015)
Objective. Synovial fluid (SF) is one of the most important materials that reflect the pathophysiological process of arthritis. A metabolomic and lipidomic study of SF was performed with the aim of identifying tentative diagnostic markers or therapeutic candidates for rheumatoid arthritis (RA). Methods. SF was aspirated from 10 patients with RA and 10 patients with osteoarthritis (OA). RA SF and OA SF were collected and analyzed by ultraperformance liquid chromatography quadruple time-of-flight mass spectrometry. Associations among clinical variables, laboratory results, and metabolic profiles were investigated. Results. The metabolic pathways for carnitine, tryptophan, phenylalanine, arachidonic acid, and glycophospholipid were significantly upregulated in OA SF. The metabolic pathways for taurine, cholesterol ester, and the beta-oxidation of pristine acid, linolenic acid, and sphingolipid were activated more in RA SF than in OA SF. In particular, the tryptophan pathway, which comprises kynurenine, indoleacetic acid, indole acetaldehyde, and N'-formylkynurenine, was downregulated. Interestingly, the levels of tryptophan metabolites kynurenine and N'-formylkynurenine, which are involved in immune tolerance, were significantly lower in RA SF compared with OA SF (p < 0.05), but the opposite pattern was observed for erythrocyte sedimentation rate (p < 0.01) and the levels of C-reactive protein (CRP; p < 0.01), rheumatoid factor (p < 0.01), and anticyclic citrullinated peptide antibody (p < 0.05). Kynurenine concentration correlated inversely with CRP concentration in RA SF but not in OA SF (r -0.65, p < 0.05). Conclusion. Advances in metabolomic techniques enabled us to delineate distinctive metabolic and lipidomic profiles in RA SF and OA SF. RA SF and OA SF showed distinct metabolic profiles.